Estudio de factibilidad para la creación de un hostal prestador de servicios turísticos en la ciudad de Manizales departamento de Caldas (2015)
Colombia is strategically located as an intermediate point between North America and South America, and within it is the only country that has coasts both in the Pacific Ocean and in the Atlantic. This geographic position allows you to have easy access to the visitors, offering beneficial opportunities for the tourism sector, improving its competitiveness. This country has departments with immense tourist potential that can be offered to a visitor. Within these departments is Caldas, where the tourist can have the opportunity to enjoy the land, culture and peaceful farms where the country's flagship crop grows. Quindío is one of the departments with the greatest tourist projection within Colombia, because of its great variety of climates and environments that it offers, has allowed the multiplication of coffee farms and haciendas, offering to the tourists accommodation and complementary services; a varied program ranging from horseback riding through old roads, to visiting typical villages and places of interest such as the snowfall of Ruiz, where you can be in contact with rural Colombia. The opportunity to expand the offer of accommodation in the city of Manizales is promoted through a feasibility study in order to know the viability of a Hostel. For this reason, the project presents in the first instance a problematic approach, which shows the existence of a flow of visitors by air and land that reach the coffee axis and especially the city of Manizales and a knowledge in the specialized area of ​​hostels and specialized accommodation systems, as well as the way to meet guests or national and international tourists.